2019
DOI: 10.1155/2019/1919082
|View full text |Cite
|
Sign up to set email alerts
|

Beyond T Cells: Understanding the Role of PD-1/PD-L1 in Tumor-Associated Macrophages

Abstract: Programmed cell death protein 1 (PD-1) and its ligand PD-L1 have attracted wide attention from researchers in the field of immunotherapy. PD-1/PD-L1 have been shown to exist in many types of cells in addition to T lymphocytes, and studies have accordingly extended from their suppressive effect on T cell activation and function to examining their role in other cells. In this review, we summarize recent research on PD-1/PD-L1 in macrophages, with the aim of furthering our understanding of PD-1/PD-L1 and their de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 48 publications
0
92
0
5
Order By: Relevance
“…As PD‐L1 does not act alone and future studies should consider the expression of its receptor, PD‐1, past studies have found that the measurement of both PD‐L1 and PD‐1 was a better predictor of survival than either factor alone (Maruse et al., 2018). PD‐L1 is also known to be expressed on tumour‐associated macrophages (TAMs), where it may encourage a M2‐phenotype, which is thought to be immunosuppressive (Lu et al., 2019). Shifting TAMs from a M2 to a M1 phenotype (proinflammatory) may be a therapeutic option in cancers, and the PD‐1/PD‐L1 pathway may be a potential target for this (Lu et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As PD‐L1 does not act alone and future studies should consider the expression of its receptor, PD‐1, past studies have found that the measurement of both PD‐L1 and PD‐1 was a better predictor of survival than either factor alone (Maruse et al., 2018). PD‐L1 is also known to be expressed on tumour‐associated macrophages (TAMs), where it may encourage a M2‐phenotype, which is thought to be immunosuppressive (Lu et al., 2019). Shifting TAMs from a M2 to a M1 phenotype (proinflammatory) may be a therapeutic option in cancers, and the PD‐1/PD‐L1 pathway may be a potential target for this (Lu et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…PD‐L1 is also known to be expressed on tumour‐associated macrophages (TAMs), where it may encourage a M2‐phenotype, which is thought to be immunosuppressive (Lu et al., 2019). Shifting TAMs from a M2 to a M1 phenotype (proinflammatory) may be a therapeutic option in cancers, and the PD‐1/PD‐L1 pathway may be a potential target for this (Lu et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor associated macrophages (TAM) are the most abundant immune cells and are known to differentially regulate tumor progression [ 22 , 23 ]. TAM also express both PD-1 and PD-L1 on their cell surface [ 24 ]. The tumor supportive “M2” macrophages express higher levels of PD-1 as compared with tumor suppressive “M1” macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that signaling via CD40 promotes IL-9 receptor expression on the surface of mBCs, and IL-9 promotes differentiation mBCs into PCs through the IL-9 receptor [1,82]. B7H-2 binds ICOS found on CD4/CD8 T cells, and enhances secretion of IFN-γ and IL-10, which sustain immune balance [84][85][86][87][88].…”
Section: B-2 Cellsmentioning
confidence: 97%